Adenoviral vectors transduce alveolar macrophages in lung cancer models. (3rd June 2018) - Tippimanchai, Darinee D.; Nolan, Kyle; Poczobutt, Joanna; Verzosa, Gregory; Li, Howard; Scarborough, Hannah; Huang, Jing; Young, Christian; DeGregori, James; Nemenoff, Raphael A.; Malkoski, Stephen P.
ABSTRACT: Adenoviral vectors expressing Cre recombinase are commonly used to initiate tumor formation in murine lung cancer models. While these vectors are designed to target genetic recombination to lung epithelial cells, adenoviruses can infect additional cell types that potentially influence tumor development. Our goal was to explore the consequences of adenoviral-mediated alveolar macrophage (AM) transduction in a Kras-initiated lung tumor model. As expected, treatment of animals harboring the Kras LSL-G12D allele and an inducible green fluorescence protein (GFP) tracking allele with an adenoviral vector expressing Cre recombinase under the control of the cytomegalovirus (CMV) promoter (Ad5-CMV-Cre), caused GFP-positive lung adenocarcinomas. Surprisingly, however, up to 70% of the total GFP + cells were AM, and GFP + AM could be detected 6 months after tumor initiation, and transduced AM demonstrated Kras activation and increased proliferation. In contrast, recombination was not detected in other immune cell populations and AM recombination could be eliminated by tumor initiation with an adenovirus expressing Cre recombinase under the control of the surfactant protein C (SPC) promoter. In addition, AM isolated from Kras LSL-G12D animals and transduced by Ad5-CMV-Cre ex vivo displayed prolonged survival in vitro and increased the growth of murine lung adenocarcinoma CMT/167 cells when co-injected in an orthotopic flank model. Given the importance of the immune system in tumor development and progression, inadvertent AM transduction by Ad5-CMV-Cre merits careful consideration during lung cancer model selection particularly if studies evaluating the tumor-immune interactions are planned.